An expert system for automating image and video editing services using AI, cloud and blockchain technologies - Xuan, Nguyen Duc; Khang, Nguyen Ngoc; Khanh, Pham Van (Edelweiss Applied Science and Technology, 2025)
In the digital age, high-quality visual content plays a critical role in marketing, real estate, and personal branding. However, traditional image and video editing workflows remain manual, fragmented, and time-consuming. This paper proposes an expert system that automates the entire service chain of photo, video, and virtual architectural editing by integrating advanced technologies such as AI, chatbots, cloud computing, and blockchain. The system intelligently analyzes customer requests, assigns tasks to AI modules or human editors, ensures quality control, and securely manages payments through smart contracts. Designed as a cloud-native, microservice-based architecture, the platform is scalable and resilient, offering services through both web and mobile interfaces. Simulation results show a significant reduction in turnaround time, enhanced consistency in output quality, and increased processing capacity. By automating both technical and operational processes, the proposed system aims to transform digital content services into a seamless, efficient, and trusted experience. It has strong potential to attract customers and investors, especially in industries demanding fast, cost-effective, and scalable media solutions.